2014
DOI: 10.2224/sbp.2014.42.9.1483
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Institutional Responsiveness on the Relationship Between Green Leadership and Green Competitiveness

Abstract: With a growing focus among firms globally on saving energy and increasing environmental awareness, it is critical to explore the implementation of corporate greening in subsidiaries of multinational companies. Multinational companies need to respond simultaneously to institutional requirements and pressures for corporate greening. In this study we utilized the natural-resource-based view to investigate how green leadership can enhance green competitiveness. Based on a quantitative analysis of 212 subsidiaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In contrast to the green resource and energy/climate CSRHub objectives, environmental policy and reporting objectives depend much less on operational management decisions (Corbett and Klassen, 2006), relying more directly on transparent disclosure efforts (Kalin and Schuldt, 1991), explicit interests in others (Ilg, 2019) and overt displays of introspection (Lee et al, 2014). Self-awareness, coupled with a sense of organizational interdependency, is fundamental to such informed disclosure (Thornton et al, 2016), as demonstrated in numerous controlled settings (c.f.…”
Section: Fit As a Principle For Om Environmental Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the green resource and energy/climate CSRHub objectives, environmental policy and reporting objectives depend much less on operational management decisions (Corbett and Klassen, 2006), relying more directly on transparent disclosure efforts (Kalin and Schuldt, 1991), explicit interests in others (Ilg, 2019) and overt displays of introspection (Lee et al, 2014). Self-awareness, coupled with a sense of organizational interdependency, is fundamental to such informed disclosure (Thornton et al, 2016), as demonstrated in numerous controlled settings (c.f.…”
Section: Fit As a Principle For Om Environmental Leadershipmentioning
confidence: 99%
“…Interest in environmental leadership has grown significantly, both in practice and across various disciplines in the academy (Sharma and Vredenburg, 1998;Avolio et al, 1999;Lee et al, 2014;Vera and Crossan, 2004;Thornton et al, 2016;Vlachos et al, 2017;Ilg, 2019). Although Corbett and Klassen note that environmental leadership "is provoking a powerful paradigm shift" (2006, p. 5) in how operations management (OM) norms and cultures have advanced from the highest levels of organizations, the topic has received more selective attention in the OM domain (Porter and van der Linde, 1995;King and Lenox, 2001;Rothernberg et al, 2001;Cheung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other recent research similarly found that institutional pressures stem from both the parent company and host country's context, thereby heaping operational difficulty on the subsidiary and forcing it to adopt strange norms (Yi et al, 2013;Hsu et al, 2014;Yang and Su, 2014;Nell et al, 2015;Carney et al, 2016;Li and Ding, 2017). Earlier ID research likewise shows that MNC subsidiaries are confronted by huge external pressures, as they navigate between countries (DiMaggio and Powell, 1983;Scott, 1995;Devinney et al, 2000;Edwards et al, 2002;Paik and Sohn, 2004;Hillman and Wan, 2005;Husted and Allen, 2006;Tempel et al, 2006;Karhunen, 2008;Marin and Costa, 2013;Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…MNC makes efforts to organize and gainer more resources such as managerial talent so as to acquire resources for competitive advantage (Johnston and Menguc, 2007). Leadership that encourages a corporation to make maximum use of natural resources mitigates external threats due to available built-up capacity (Lee et al, 2014). Companies gain competitive and resource advantages by political application of corporate social responsibility schemes (Frynas and Stephens, 2015).…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation